The role of Livonian in Latvia from a sociolinguistic perspective - Ina Druviete; Gunta Kļava (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2018)
This article examines the role of Livonian in present-day Latvia and describes the Livonian language situation in the context of Latvia’s language situation and current sociolinguistic issues. It describes how Livonian language and culture are represented in Latvian law, along with possibilities for realising Livonian language rights, bringing attention to the Livonians as an ethnicity, and understanding issues relating to Livonian, while also describing the use of terminology in the Livonian context. The Livonians cannot exactly be described as a “minority”. The Livonians are something more, they are a part of the modern Latvian language and also of Latvian culture and the culture of Latvia in general. And yet, the Livonian nation and language are independent entities. Therefore, the position of Livonian within Latvia should be seen from two perspectives: the preservation, development, and revitalisation of the use of Livonian as well as the mutual influence of Livonian and Latvian.